Quercetin with lycopene modulates enzymic antioxidant genes pathway in isoproterenol cardiotoxicity in rats: Cardioprotection by quercetin & lycopene. Issue 1 (1st January 2021) - Chen, LIJUAN; Wu, XIAOLI; Wang, WEIWEI; Wang, XIA; Ma, Jianhua
ABSTRACT: Quercetin (QN) is a naturally occurring phenolic compound found largely in vegetables and fruits. Lycopene (LY) is yet another natural phytocompound, found abundantly in red-colored fruits and vegetables. Both have been reported to have beneficial activities in humans. In this study, we document in vivo experimental model for isoproterenol (ISO) cardiac injury toxicity in Sprague-Dawley (SD) rats and treatment with a combined optimized concentration of quercetin and lycopene (QL). Male SD rats of different groups were treated with QL (80 mg/kg QN and 3 mg/kg LY together p.o .) for 10 days with ISO administration (100 mg/kg i.p .) on days 7 and 8. After experimental period, CK-MB, TROP, AST, ALT, LDH, GST, GPx, CAT, SOD, Vit.E, Vit. C, GSH, GSSG and MDA were estimated. SD rats administered with ISO showed an obvious rise in the serum marker enzyme levels and tissue oxidative stress markers (MDA and GSSG). Furthermore, marked reductions in the body weight and increases enzymic and non-enzymic antioxidant levels were noticed. Histological features of the heart also indicated a disruption in the cardiac myofibrils structure of ISO-intoxicated rats. Also, quantitative PCR analysis revealed an involvement of antioxidant and related pathway genes such as Nrf2, HO-1, NQO1, GSTµ, SOD1, SOD2, CAT and BCl-2 genes. QL pretreatment prevented all these adverse effects of ISO cardiotoxicity and significantly reduced the myocardial damage. Decrease in oxidative stress was observed, possibly through alterations in the expression levels of enzymic antioxidant genes (GSTµ, SOD1, SOD2 and CAT). In general, QL exert a strong protective effect through the modulations in enzymic antioxidant activity and associated molecular pathways-regulating effect in cardiovascular disease.